2021
DOI: 10.1002/cbdv.202000949
|View full text |Cite
|
Sign up to set email alerts
|

Eremophilane Sesquiterpenes and Benzene Derivatives from the Endophyte Microdiplodia sp. WGHS5

Abstract: Three new eremophilane sesquiterpenes phomadecalins G−I (1–3) and two new benzene derivatives microdiplzenes A and B (12 and 13), together with nine known eremophilane sesquiterpenes (4–11 and 14) were isolated from an endophytic fungus, Microdiplodia sp. WGHS5. Their structures were elucidated by the interpretation of HR‐ESI‐MS and NMR data; meanwhile, the absolute configurations of new compounds were determined on the base of ECD calculations. All compounds were evaluated for the antimicrobial activities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The configurations at C-11 of compounds 319 , and 321 – 323 are not determined. The CD spectra of acemeremophilane A ( 317 ), 58 phomadecalin H ( 318 ), 135 and phomadecalin G ( 320 ) 135 were measured. The numbering system used in acemeremophilane A ( 317 ) was changed to the present system.…”
Section: Discussionmentioning
confidence: 99%
“…The configurations at C-11 of compounds 319 , and 321 – 323 are not determined. The CD spectra of acemeremophilane A ( 317 ), 58 phomadecalin H ( 318 ), 135 and phomadecalin G ( 320 ) 135 were measured. The numbering system used in acemeremophilane A ( 317 ) was changed to the present system.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of isolated compounds on the HeLa and MCF-7 cells were assessed in vitro by using the MTT assay on a 96-well plate. Experimental details of test used in this study are summarized in previous reports [ 21 , 22 ]. The toxicities against normal LO2 and HaCaT cells were tested via the cell counting kit-8 (CCK-8) method, similar to the reported reference [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results revealed that 87 had equivalently effective antifungal activity against B. cinerea and F. graminearum at 100 μg/mL. [ 47 ].…”
Section: Sesquiterpenoids Typesmentioning
confidence: 99%